Pengembangan Perangkat Pembelajaran Cooperative Integrated Reading And Composition Untuk Meningkatkan Pemahaman Geometri - andang, andang; Hadi, Arnasari Merdekawati; Wirahmad, Ika (AKSIOMA : Jurnal Matematika dan Pendidikan Matematika, 2018)
Mathematics is a universal science underlying the development of modern technology, has an important role in various disciplines and advance the human mind. Mathematics subjects in addition to having abstract nature it also requires a good understanding. In general at school, the teacher is still the center of the delivery of the material, the source of learning is the teacher’s handbook, concentrating toomuch on the exercise of solvin g a more procedural mechanistic problem rather than inculcating an understanding. The purpose of this research are 1) to produce learning device with cooperative integrated reading and composition in order to increase understanding of gemetry, and 2) know the student’s response to the learning device that has been developed. This type of research is research development with model ploomp. Subjek field trial includes 32 students of class VIII7 in SMPN 1 Bima city. Instrument research used consisted of validation sheet, observation sheet teaching implementation, student activity observation sheet, student’s response haunter, teacher research questionnaire, and concept comprehension test, result of product assesment is a RPP draft, LKS and student learning module by using quantitative and qualitative data analysis. Assessment used by finding the mean value of all aspect of prototypt assessment by validator 4,6 with qualitative criteria is very valid. Date student activity obtained score to idea of 98,84%. Avarage ability of teachers in learning process 4,26 and are in good category, more than 95% of students responded by saying interested and are interested in learning, and the understanding of geometry (circle) avarages is 85,43 with classical completeness equal to 87,09%.  Key Word: Learning device, cooperative CIRC, understanding of geometry.